La utilización de las narraciones e historias en la práctica docente - Alonso García, Miguel Aurelio; Calles Doñate, Ana María (Cuadernos de Trabajo Social, 2008)
The article proposes the use of storytelling in teaching practice and justified as a useful metodology in the face to increased motivation, learning and changing certain behaviors in students. It recount different experiences in which concrete have been used in contexts teaching narrations, specifying the methodology and results achieved to facilitate the use by the reader.